Metacontrast masking of symmetric stimuli - Giulio Contemori; Marianna Musa; Carolina Maria Oletto; Stefano Vicentin; Luca Battaglini; Giorgia Cona; Marco Bertamini (PLoS ONE, 2025)
This study investigated whether symmetry perception is vulnerable to metacontrast masking and whether such masking selectively disrupts feedback-dependent visual processes. Across four experiments, we employed a metacontrast paradigm with briefly presented targets (20 ms) followed by masks at varying stimulus onset asynchronies (SOAs), manipulating both target–mask configuration and task demands. All experiments produced the classic U-shaped accuracy-by-SOA curve associated with Type B masking, where performance is lowest at intermediate SOAs. Critically, performance at 0 ms SOA varied depending on the perceptual compatibility of the stimuli. In Experiments 1 and 2, the target and mask were spatially complementary and could be perceptually grouped into a unified figure. Under these conditions, performance at 0 ms SOA exceeded the no-mask baseline, reflecting facilitation due to perceptual integration. In contrast, in Experiments 3 and 4—where the stimuli and mask had no complementary shape and could not be integrated into a coherent object—performance at 0 ms SOA was slightly suppressed, indicating that integration failed to occur. These findings suggest that facilitation at short SOAs depends on the rapid formation of a coherent perceptual object, whereas symmetry detection—requiring temporally extended, feedback-supported integration—is more susceptible to early interruption by masking. Together, these results support both dual-channel and recurrent models of visual masking. Type B suppression reflects interactions between fast feedforward and slower feedback signals, while the presence or absence of early facilitation serves as an index of perceptual organization. These findings underscore how stimulus structure and task context affect the temporal dynamics of shape perception.